2018
DOI: 10.1021/acsami.8b01651
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of NixSe (0.5 ≤ x ≤ 1) Nanocrystals for Efficient Rechargeable Zinc–Air Batteries and Water Splitting

Abstract: The development of earth-abundant, highly active, and corrosion-resistant electrocatalysts to promote the oxygen reduction reaction (ORR) and oxygen and hydrogen evolution reactions (OER/HER) for rechargeable metal-air batteries and water-splitting devices is urgently needed. In this work, Ni Se (0.5 ≤ x ≤ 1) nanocrystals with different crystal structures and compositions have been controllably synthesized and investigated as potential electrocatalysts for multifunctional ORR, OER, and HER in alkaline conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(84 citation statements)
references
References 54 publications
11
73
0
Order By: Relevance
“…Therefore, many efforts have been devoted to design and fabricate nonprecious metal electrocatalysts for HER. Over the past few years, nonprecious metal–based electrocatalysts such as transition metal sulphides, selenide, nitrides, phosphides, and carbides have been developed as good candidates for HER.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many efforts have been devoted to design and fabricate nonprecious metal electrocatalysts for HER. Over the past few years, nonprecious metal–based electrocatalysts such as transition metal sulphides, selenide, nitrides, phosphides, and carbides have been developed as good candidates for HER.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high cost, terrestrial scarcity and non-bifunctional property impede their widespread utilization [4][5][6]. During the past decades, non-noble metal oxides, hydroxides, chalcogenides, phosphides and nitrides have attracted special attention as bifunctional catalysts for OER and HER due to their cost-competitiveness, high abundance and environmental friendliness [7][8][9][10][11][12][13][14]. Unfortunately, their electrochemical properties are still far away from that of noble metal catalysts due to the limited active sites and poor electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Subbarao et al revealed that NiSe prepared by ball milling has a slightly better activity compared to the same composition synthesized by solution procedure. Moreover, Zheng et al found promising potential applications for nickel selenide nanocrystals as earth‐abundant and high‐performance electrocatalysts for metal‐air batteries and alkaline water splitting. Tang et al used NiSe Nano wire film on nickel foam as an electrode for high‐performance supercapacitors.…”
Section: Introductionmentioning
confidence: 99%